Analisis Peran Keuangan Mikro Syariah terhadap Kesejahteraan Masyarakat Desa - Sapna Maharani Saragih; Sri Wahyuni (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
Microfinance institutions can enhance the standard of living in villages through principles of justice, partnership, and mutual assistance. Data were collected through in-depth interviews with Islamic microfinance institution managers and beneficiaries in several rural areas. The findings indicate that Islamic microfinance has a positive impact on the economic well-being of rural communities, particularly by providing access to interest-free (riba-free) funding for small businesses, increasing household income, and strengthening the local economy. Furthermore, the presence of Islamic microfinance promotes more responsible economic behavior aligned with Islamic values. Financial education initiatives provided by the institutions also contribute to improving the financial literacy of villagers. In conclusion, Islamic microfinance serves as a vital tool in empowering rural communities through sustainable, fair, and Sharia-compliant economic development.